Avaliação da capacidade física e qualidade de vida em sujeitos com doença arterial obstrutiva periférica - Nascimento, Abraão Sérvulo (2016)
Introduction: Peripheral arterial occlusive disease (PAOD) leads to decreased blood flow in the lower limbs and, consequently, intermittent claudication (IC) during physical activity or exercise leading to worsening of physical capacity and quality of life. Objective: The aim of the study was to evaluate physical capacity and quality of life of individuals with PAOD living in Santa Cruz-RN. Methodology: Subjects aged 60 to 80 years showing the ankle-brachial index (ABI) <0.9 in the presence or absence of IC were included in the study. Firstly, individuals were assessed through a structured evaluation form and answered the Short Form questionnaire (36) Health Survey. Then they performed the following tests: 6-minute walking test, incremental shuttle walking test and heel-rise test. Results: Of the 128 elderly recruited, 20.3% (n-26) presented an ABI <0.9. Final sample consisted of 14 individuals, being 64% (n = 9) asymptomatic. Walked distance, in meters, in the 6MWT was 344.7 ± 95.1 and in the ISWT was 210 [115.0-275]. Mean HRT elevations were 20 [8.2-30.5] movements at a mean execution time of 67.5 [51.2 - 95.7] seconds. The main domains affected in the SF-36 were those related to emotional and social aspects with median of 50 [24.7-67] and 50 [47-66] points, respectively. Conclusion: Reduced physical capacity in these individuals can directly affect the quality of life of these subjects, not only regarding functionality, but social and emotionally.